Kajian Hukum Mengenai Kewenangan Dewan Perwakilan Rakyat Dalam Pengisian Jabatan Hakim Konstitusi Ditinjau Dari Prinsip Negara Hukum Dan Demokrasi Di Indonesia - Parhusip, Tania Enjelina; HB, Gusliana; Rauf, Muhammad A. (Peneliti.net, 2024)
The Constitutional Court is a state institution that was formed after the amendment to the 1945 Constitution. In this context, the Constitutional Court has a vision in enforcing the constitution which aims to create a state that strictly adheres to law and democracy in the administration of state life. The Constitutional Court has 9 (nine) constitutional judge members appointed by the President, each of whom is appointed 3 (three) people by the Supreme Court, 3 (three) people by the DPR and 3 (three) people by the President. One of the reasons for the DPR's involvement in filling the position of constitutional judge after the 1945 Constitution was the phenomenon of strengthening the DPR in the Indonesian constitutional system during the democratic transition period through changes to the 1945 Constitution. However, this involvement has the potential to give rise to a number of problems, including the existence of the DPR's authority which is very decisive in the selection process for constitutional judges can give rise to problems of politicization. The aim of this research is to determine the implementation of the authority of the People's Representative Council in filling the positions of constitutional judges based on the principles of the rule of law and democracy in Indonesia and to find out the ideal model for filling the positions of constitutional judges from the authority of the People's Representative Council in the future. The results of this research explain that first, the DPR's authority to fill the position of constitutional judge is not in accordance with the principles of democracy and the principles of the rule of law because when filling the constitutional judge, the DPR actually has full authority over the nomination of 3 constitutional judges. Second, the Recruitment and Selection Model for Constitutional Court Judges using a Selection Panel either by the respective Institution Proposing Constitutional Judges or a selection Panel in the form of an agreement with the Institution Proposing Constitutional Judges is a legal reform whose main aim is to produce constitutional judges who have the ideal integrity as a statesman Really.